An evaluation study of the preparatory year experience for medical faculties at Tishreen University from the point of view of teachers - زمرد, اميرة; بوبو, منذر (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the current research is to investigate the reality of the preparatory year at Tishreen University with all its components, and to monitor its strengths and weaknesses in order to make proposals for its development, from the point of view of a sample of its teachers. The researchers used the descriptive approach, and the research tool was a semi-directed interview, conducted with (20) teachers who taught for three years for the theoretical part of one of the preparatory year courses. The results of the research showed that the evaluation of the preparatory year teachers for it as an experiment came to a medium degree and their general satisfaction with it also came to a medium degree. In terms of their evaluation of the courses they teach, 70% of them considered that their courses are good, their content is good, related to medical specializations, and very useful to the specialization to which the student are directed with a very good degree, and that the content of book chapters is well connected. The results also confirmed that 40% of teachers believe that the course they teach it directed to medical specialties with a good degree, it directed to human medicine more than other medical specialties, and 50% of teachers think that the course they teach is very important for the preparatory year. As for the degree of satisfaction with the automated assessment method, it was an average of 35%, and teachers suggested adding practical assessment of students through interviews. With regard to presence of theoretical lectures, the largest percentage (55%) of teachers confirmed that students' presence rate is weak, and they explained this by students going to private institutes and private lessons and relying on course questions. The teachers identified the strengths in the preparatory year: the unified evaluation, the good scientific content of the courses, and giving them a new opportunity for the student after the high school certificate. As for the weaknesses, they identified them as follows: Weak infrastructure (lack of suitable halls for the number of students, lack of books...etc), central the severe and uniqueness of Damascus University in the calendar, the spread of private institutes, and the huge content. The teachers suggested solutions to these problems: providing a physical environment, de-centralizing, developing curricula...etc. (55%) of the teachers supported keeping the preparatory year experience, while (40%) saw the need to abolish it.